Reading and Mathematics Differences for English Language Learners Enrolled in Dual Language or Exit Programs - Julia D. Trevino Mendez; John R. Slate; Cynthia Martinez-Garcia (Athens Institute for Education and Research, 2017)
In this investigation, the relationship between bilingual education program type (i.e., dual language programs or exit programs) and English Language Learner reading and mathematics test scores was examined. Data were obtained on English Language Learners who were enrolled in Grades 3, 4, 5, and 6 in Texas public schools for the 2008-2009, 2009-2010, and 2010-2011 school years. In all 24 analyses, the reading and mathematics scores of English Language Learners who attended a dual language program were consistently higher than the scores of the English Language Learners who were enrolled in an exit program. As grade level increased from Grade 3 to Grade 6, the achievement gap in reading and in mathematics between dual language and exit programs also increased.